Contribution a l’étude de la reproduction et la croissance de pageot Pagellus acarne (Risso, 1827) pêché dans la baie de Mostaganem - AMAROUCH, MERIEM (My University, 2016)
Biology and population dynamics of sea bream Pagellus acarne (Risso, 1827) an economically interesting species, were studied. The evidence provided by the biological study and monthly monitoring of length frequencies were used in an attempt to determine the reproduction period, fecundity, size at first maturity and an assessment of the status of its stock. The overall sex ratio is in favor of females while its evolution over months showed significant differences (χ2, p<0.05 Following the monthly evolution of the three parameters (GSI, HSI and K) of Algerian west coast seabream showed that this sparidae has two spawning periods the first covering spring from April until mid- June with a peak in May, the second from October to December The parameters of the von Bertalanffy equation for the entire population of P. acarne off Oran bay are equal to: L∞ = 20.63 (Cm), K = 0.99 (year-1), t0 = -0.28 (year), W∞ = 91.11 (g), Φ =2.625. Growth parameters K and Φ are clearly superior to other Mediterranean areas indicating a rapid growth of the species in Mostaganem Bay. Parameter b of the length-weight relationship seems > to 3 (3.181 both sexes, 3.218 for males, and 3,187 for females), which reflects a positive allometry for the species (t-test, P<0.05). The minimum landing size (MLS) set for P. acarne is equal to 15 cm Lt, the size is greater than the length at first sexual maturity of females of the species evaluated at 12.75 cm, but it seems to be insufficient and it would be advisable to increase the MLS and set it at 17 cm ensuring renewal of the resource.
Keywords: Pagellus acarne; Reproduction; croissance; Méditerranée occidentale; baie de Mostaganem.; Growth; Western Mediterranean; Mostaganem bay.; التكاثر; النمو; غرب البحر الأبیض المتوسط; خلیج مستغانم